Poly(vinylidene fluoride-trifluoroethylene) ferroelectric polymer for non-volatile memory applications - Nguyen Anh Chien (2009)
Ferroelectric copolymer, poly(Vinylidene fluoride - trifluorine ethylene) P(VDF-TrFE), has been investigated for the application in non-volatile memory. Thin films by spincoating have been characterized for changes in surface morphology, crystalline structure and electrical properties induced by thermal annealing and corona poling. Topography of rod-like structure is correlated to the film semi-crystallinity which is strongly dependent on thermal annealing and can be modified into better order by corona poling. Measurements of dielectric properties below glass transition temperature lead to findings of free charge carrier concentration and interface charge density in the P(VDF-TrFE) film that are matched to devices formed by interfacing with semiconductor layer.